Building Structural Systems in Christchurch's Post-Earthquake Reconstruction. Issue 4 (November 2019) - Bruneau, Michel; MacRae, Gregory
After the 2010–2011 Canterbury earthquakes, much of the Christchurch Central Business District was demolished, and a new city is in the process of emerging in its place. A series of interviews conducted with key professionals involved with the reconstruction, together with data collected from various sources (including Christchurch's City Council database), has made it possible to (1) quantify variations in the selection of a structural system as a function of various parameters and (2) identify some of the drivers that have influenced decisions about the selection of structural material and specific structural systems used. Key points on factors that may affect post-earthquake structural engineering practice are drawn from the data collected. As such, the Christchurch rebuilding experience provides insights into some of the mechanisms that can dictate structural engineering decisions during the post-earthquake reconstruction of a modern city.